Ballistic performance of TPU/steel configurations against spherical projectiles - Ievgen Levadnyi; Fujia Liu; Yaodong Gu (AIP Advances)
In this work, we numerically and experimentally investigate the ballistic performance of thermoplastic polyurethane (TPU)/steel configurations against spherical projectiles. We chose TPU materials with high and low hardness values to form the impact-sustaining layer to investigate the ballistic performance of protective configurations. Experiments were performed by using a powder gun that shot spherical projectiles, each with a diameter of 8.4 mm, at velocities ranging from 250 to 400 m/s. A typical plug formation was observed as the failure mode of steel plates under all configurations, and we obtained curves of the ballistic limit of each configuration. The ballistic performance of the best design, featuring a TPU material with a high hardness value, was 5.8% better than that of a monolithic plate. We also separately tested materials to calibrate their models for numerical simulations. Numerical models of projectile–target systems were established by using Abaqus software and validated based on the experimental results. The results of the simulations were in good agreement with those of the experiments in terms of the failure mechanism of the configurations and residual velocity of the projectiles. Furthermore, we developed a mathematical model to accurately predict the residual velocity of the projectile after having perforated the TPU/steel configuration. It considers the thickness and hardness of the layers and the weight and initial velocity of the projectile. The predictions of our model yielded a high correlation coefficient and a low mean squared error with the results of simulations.